Criteria for Assessing Subjective Well-Being - Hakobyan, Naira; Sotnyk, Iryna; Khachatryan, Anna; Gasparyan, Elen (ՀՀ ԳԱԱ)
Modern psychological, economic, and social processes are characterized mainly by stress-producing features. Today, the psyche of a modern person is exposed to powerful negative impacts of social, psychological, man-made, natural, every day, and many other nature, which require special measures to protect mental health and strengthen it. In this context, studying and analyzing emotional well-being is becoming increasingly important. The concept and methodology of ensuring subjective well-being in the context of overcoming stress-producing effects of the external environment, highlighting the deep features of the relationship between social stability and subjective well-being, the search for practical ways are today, more than ever, on the agenda, relevant and urgent. Proof of this is scientific evidence of the transformation processes of modern societies, in which the individual, like social groups, regularly face complex and contradictory socio-psychological, economic, cultural, and civilizational processes. In such situations, manifestations characteristic of the phenomenon of anomie of personality and social groups develop and deepen, the normative system of behavior management of individuals is absent or levels out, the processes of self-realization of the individual, disclosure of personal potential, formation of a constructive attitude to reality and experience of subjective well-being are hampered. Psychological features and emotional-evaluative components that determine the internal comfort and balance of the individual are transformed, which inevitably affects the individual’s subjective well-being, behavior, and life. Based on the fact that the attention of the scientific community to the problems of subjective well-being is currently emphasized, it is becoming increasingly difficult to classify the signs characteristic of the phenomenon under study, which, in turn, leads to distortions in the general perception of subjective well-being. Therefore, the relevance of this study is due to the need to present a scientific concept of criteria formation for assessing subjective well-being. Ժամանակակից հոգեբանական, տնտեսական և սոցիալական գործընթացները բնութագրվում են հիմնականում սթրեսածին հատկանիշներով: Այսօր ժամանակակից անձի հոգեկանը ենթարկվում է սոցիալական, հոգեբանական, տեխնածին, բնական, կենցաղային և շատ այլ բնույթի հզոր բացասական ազդեցությունների, որոնք պահանջում են հատուկ միջոցներ հոգեկան առողջության պահպանման ևամրապնդման համար: Սուբյեկտիվ բարեկեցության ապահովման հայեցակարգը և մեթոդաբանությունը արտաքին միջավայրի սթրեսածին ազդեցությունների հաղթահարման համատեքստում, ընդգծելով սոցիալական կայունության և սուբյեկտիվ բարեկեցության փոխհարաբերությունների խորքային առանձնահատկությունները, գործնական ուղիների որոնումն այսօր, առավել քան երբևէ, օրակարգային են՝ տեղին և հրատապ: Դրա ապացույցը ժամանակակից հասարակությունների տրանսֆորմացիոն գործընթացների մասին գիտական վկայություններն են, որտեղ անհատը, ինչպես սոցիալական խմբերը, պարբերաբար բախվում են բարդ և հակասական սոցիալ- հոգեբանական, տնտեսական, մշակութային և քաղաքակրթական գործընթացներին: Նման իրավիճակներում զարգանում և խորանում են անձի և սոցիալական խմբերի անոմիայի երևույթին բնորոշ դրսևորումները, բացակայում կամ թուլանում է վարքագծի կառավարման նորմատիվ համակարգը, խաթարվում են անձի ինքնաիրացման գործընթացները, անձնական ներուժի ևիրականության նկատմամբ կառուցողական վերաբերմունքի ձևավորման փորձառությունը: Վերափոխման են ենթարկվում նաև հոգեբանական առանձնահատկությունները, հուզական- գնահատական բաղադրիչները, որոնք պայմանավորում են անձի ներքին հարմարվողականությունն ու հավասարակշռությունը, ինչը անխուսափելիորեն ազդում է անհատի բարեկեցության, վարքի և կյանքի սուբյեկտիվ զգացողության վրա։ Ելնելով այն փաստից, որ ներկայումս ընդգծված է գիտական հանրության ուշադրությունը սուբյեկտիվ բարեկեցության խնդիրների վրա, գնալով դժվարանում է դասակարգել ուսումնասիրվող երևույթին բնորոշ նշանները, ինչը, իր հերթին, հանգեցնում է սուբյեկտիվ բարեկեցության ընդհանուր ընկալման աղավաղումների: Ուստի, այս ուսումնասիրության արդիականությունը պայմանավորված է սուբյեկտիվ բարեկեցության գնահատման չափանիշների ձևավորման գիտական հայեցակարգի ներկայացման անհրաժեշտությամբ։
Keywords: Psychology